Educational Assimilation Strategies in Building an Inclusive Civilization in the Midst of Pakistan's Divided Society: A Systematic Literature Review - Fauzan Addinul Jihad; Mutohharun Jinan (Universitas Islam Negeri Sumatera Utara, 2026)
This study aims to analyze the strategies of assimilation of education in Pakistan to build an inclusive civilization in a divided society while identifying knowledge gaps in the existing literature. The core problem lies in the fragmented education system, which creates